DETERMINING STANDARD TIME OF PRACTICUMS IN MAINTENANCE DOMESTIC AIR CONDITIONING SYSTEM FOR VOCATIONAL SCHOOLS STUDENT - Miftakhudin, Muhammad; Suherman, Amay; Berman, Ega Taqwali (Universitas Pendidikan Indonesia, 2020)
Maintenance of the domestic air-conditioning system is a basic competency that exists in the refrigeration and air-conditioning expertise program. At present there is no set standard for the time students have to take in one practice training in maintaining the domestic air conditioning system. This study aims to obtain standard time practicum in maintenance domestic air conditioning systems for vocational scholls student. This study describes the standard time results of maintenance work on the domestic air conditioning unit using a quantitative approach with pre experimental design. Data collection uses test and observation instruments, where time measurement uses the stopwatch. The results showed that the standard time for maintaining an ideal domestic air conditioning system for students to achieve competence was 49.18 minutes. The standard timecan be reached after students repeat the practice of maintaining the domestic air conditioning system three times. This research complicates the students' self-confidence is increasing in the practice of maintaining the domestic air conditioning system.